(untitled) (American Journal of Islam and Society, 2013)
This excellent edited collection unpicks and disputes multifarious and intricate processes that underpin the homogenization, otherization, and vilification of immigrants from Muslim-majority countries, Muslim citizens, and individuals with a Muslim cultural background in the group of countries known as “the West.” It does so through presenting a selection of essays that offer an insight into the localized, day-to-day realities of people whose lives are currently defined by their link to Islam. The focus on gender, home, and belonging emphasizes the particular challenge faced by Muslim women: Their bodies are the battleground for the ideological wars fought by western governments on the one hand, and by political Islamists on the other (pp. 30-31). At the same time, media outlets and governmental policies portray and essentialize all Muslims as a single, uniform community defined exclusively by their Muslimness, thereby ignoring any of their differences based on “national origin, rural-urban roots, class, gender, language, lifestyle and degree of religiosity, as well as political and moral conviction” (p. 2). As all of the essays demonstrate, these concerns about representation remain valid, despite the critiques of historical and contemporary orientalism published by Edward Said over thirty years ago notwithstanding: Orientalism (1979) and Covering Islam: How the Media and the Experts Determine How We See the Rest of the World (1981). The collection is a result of two conferences held in Toronto (2006) and Amsterdam (2008) to discuss these issues. It is organized around four themes: discourse, organizations, and policy; sexuality and family; youth; and space and belonging. The first theme is represented by different perspectives from the Netherlands, the United States, and the United Kingdom. Halleh Ghorashi analyzes the disempowering effects of supposedly “empowering courses” for immigrant women of Muslim backgrounds and indicates how women themselves critique the terms on which such courses are delivered. Fauzia Erfan Ahmed writes about the deteriorating situation for female American Muslim community leaders who are forced into silence despite a long history of female leadership since the time of slavery. Cassandra Balchin’s chapter focuses on Muslim women’s refusal to cede the discourse of their legal rights to both the governments and to patriarchal males within Muslim communities, who are ...